Challenges and Market Opportunities for Solar Energy in Saudi Arabia - Alkhaldi, Saleh Amid Saleh (Transactions on Engineering and Computing Sciences, 2024)
At present, the renewable energy sector, especially solar energy, is the world’s future destination for a clean future in terms of resource consumption. The world’s solar obsession, and the quest for the best use of sunlight, are of particular interest to countries in the world and Saudi Arabia. Although sunlight is highly suitable in Saudi Arabia compared to other countries, it still pays large sums for traditional energy sources. Saudi Arabia experienced significant population and economic growth in recent years, a direct result of an increase in consumption of traditional energy sources, which poses a major threat to the country’s economy, as well as the negative environmental impacts of the use of non-renewable energy sources. The following points are the outputs of the study: Reviewing previous projects on solar energy in Saudi Arabia, comparing the performance of photovoltaic solar power systems from concentrated solar power systems in Saudi Arabia, and studying the structure of the solar energy sector in Saudi Arabia, as well as the challenges and opportunities in the solar energy sector to reach recommendations that would support the transition towards renewable energy in Saudi Arabia. For this purpose, a questionnaire was developed to strengthen the solar energy sector and formulate recommendations. The SWOT analysis was used to understand the strengths and weaknesses of the solar sector in the Kingdom, as well as the opportunities and threats facing the sector. Results of SWOT analysis revealed that Saudi Arabia citizens are aware about climate change and want to shift to renewable energy, but the cost of renewable energy transformation for end users is not cheap, among other results. One of the most significant opportunities in Saudi Arabia is the Vision 2030 that focuses on Renewable Energy transformation, while the economic feasibility of renewable energy projects is considered a major challenge. Renewable Energy projects in Saudi Arabia can contribute to 2.1% reduction in local CO2 emissions.